The Role of Gadgets in Shaping Motivation and Learning Outcomes of Junior High School Students - Abdul Kadir, Nosy Restia; Santiani; Muhtadin (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study investigates the role of gadgets in enhancing learning motivation and improving academic outcomes among junior high school students. Employing a mixed-methods approach, quantitative data from surveys and qualitative insights from interviews were analyzed to explore students’ experiences when incorporating digital devices into their learning processes. The findings indicate that effective integration of gadgets in classroom settings significantly bolsters students’ learning motivation, which in turn mediates higher academic achievement. Furthermore, mobile learning readiness, especially in science subjects, facilitates access to interactive digital content that increases student engagement and positively impacts learning outcome. The study underscores the critical role of educators in guiding technology use to maximize its benefits, and it advocates for a strategic implementation of digital tools to enhance contemporary educational practices.